Is notation for the Hammond organ a help or a constraint? - Boyle, Alex (2023)
This commentary explores the notational demands of composing for the Hammond organ. The aims of this research have been to develop existing notation for the Hammond, find new performance techniques for the instrument with notation for these, and to develop a notation system to suit the specific needs of the Hammond organ in contemporary classical music. Also, to explore the relationship between composer and performer when writing for the Hammond organ, a relationship that needs to balance the composer’s desire for structure with the performer’s freedom of artistic expression. My compositions for this project are Philly ‘63 for Hammond organ and jazz orchestra and Seven Last Words from the Cross for solo Hammond organ. The notation of these pieces contrast greatly. Philly ‘63 uses an adaptation of conventional left to right music notation and allows artistic freedom for the organist to improvise within guidelines. Seven Last Words from the Cross uses a hybrid notation system of flowchart systems with established music notation conventions and allows the organist freedom in interpretation only.